Brucella abortus in Kazakhstan, population structure and comparison with worldwide genetic diversity - Shevtsov, Alexandr; Cloeckaert, Axel; Berdimuratova, Kalysh; Shevtsova, Elena; Shustov, Alexandr V.; Amirgazin, Asylulan; Karibayev, Talgat; Kamalova, Dinara; Zygmunt, Michel S.; Ramanculov, Yerlan; Vergnaud, Gilles (Frontiers in Microbiology, 2023)
Brucella abortus is the main causative agent of brucellosis in cattle, leading to severe economic consequences in agriculture and affecting public health. The zoonotic nature of the infection increases the need to control the spread and dynamics of outbreaks in animals with the incorporation of high resolution genotyping techniques. Based on such methods, B. abortus is currently divided in three clades, A, B, C. The latter includes subclades C1 and C2. This study presents the results of whole genome sequencing of 49 B. abortus strains isolated in Kazakhstan between 1947 and 2015 and of 36 B. abortus strains of various geographic origins isolated from 1940 to 2004. In silico Multiple Locus Sequence Typing (MLST) allowed to assign strains from Kazakhstan to subclades C1 and to a much lower extend C2. Whole genome Single Nucleotide Polymorphism (wgSNP) analysis of the 46 strains of subclade C1 with strains of worldwide origins showed clustering with strains from neighboring countries, mostly North Caucasia, Western Russia but also Siberia, China and Mongolia. One of the three Kazakhstan strains assigned to subclade C2 matched the B. abortus S19 vaccine strain used in cattle, the other two were genetically close to the 104M vaccine strain. Bayesian phylodynamic analysis dated the introduction of B. abortus subclade C1 into Kazakhstan to the 19th and early 20th centuries. We discuss this observation in view of the history of population migrations from Russia to the Kazakhstan steppes.